Flache Erfahrungskurvenprofile von ausländischen Beschäftigten in Deutschland; Flat experience curve profiles of foreign employees in Germany - Stephan Brunow; Oskar Jost (Wirtschaftsdienst, 2021)
Dieser Beitrag widmet sich der Entlohnungsstruktur von ausländischen und deutschen sozialversicherungspflichtig Vollzeitbeschäftigten und zielt auf die Lohnzuwächse durch die Aneignung von zusätzlicher Erfahrung auf dem deutschen Arbeitsmarkt. Bisherige Erkenntnisse für Deutschland deuten darauf hin, dass Arbeitsmarkterfahrung bei Ausländern im Vergleich zu deutschen Beschäftigten zu keinen oder nur geringen Lohnzuwächsen führt. Wir identifizieren und diskutieren Ursachen und Erklärungen für diese flacheren Erfahrungskurvenprofile, was insbesondere vor dem Hintergrund der Einkommensungleichheit zwischen beiden Gruppen relevant ist. – – This paper sheds light on the wage structure of foreign and German employees who are subject to social security contributions in fulltime employment and focuses on the experience structure. Existing evidence suggests that additional labour market experience is rewarded less for migrants than for their German counterparts. We identify and discuss reasons and explanations for migrants' flat experience curves, which is particularly important in the light of the debate on inequality between both groups. These explanations include: the recognition of vocational training degrees, the successful passing of vocational training in Germany, German citizenship by naturalisation, and the labour market experience. After ten to 15 years in the German labour market, we identify convergence in the returns to labour market experience.
Keywords: J15; J31; J44; 330; Arbeitsmarkt; Arbeitsmigranten; Lohn; Einkommen; Deutschland